Dietary intake of fructose increases purine de novo synthesis: A crucial mechanism for hyperuricemia - Zhang, Pengfei; Sun, Huimin; Cheng, Xinyu; Li, Yajing; Zhao, Yanli; Mei, Wuxuan; Wei, Xing; Zhou, Hairong; Du, Yunbo; Zeng, Changchun (Frontiers in Nutrition, 2022)
Background: Fructose consumption is a potential risk factor for hyperuricemia because uric acid (UA) is a byproduct of fructose metabolism caused by the rapid consumption of adenosine triphosphate and accumulation of adenosine monophosphate (AMP) and other purine nucleotides. Additionally, a clinical experiment with four gout patients demonstrated that intravenous infusion of fructose increased the purine de novo synthesis rate, which implied fructose-induced hyperuricemia might be related to purine nucleotide synthesis. Moreover, the mechanistic (mammalian) target of rapamycin (mTOR) is a key protein both involved in fructose metabolism and purine de novo synthesis. The present study was conducted to elucidate how fructose influences mTOR and purine de novo synthesis in a hepatic cell line and livers of mice. Methods: RNA-sequencing in NCTC 1469 cells treated with 0- and 25-mM fructose for 24 h and metabolomics analysis on the livers of mice fed with 0- and 30- g/kg fructose for 2 weeks were assessed. Gene and protein expression of phosphoribosyl pyrophosphate synthase (PRPSAP1), Glutamine PRPP aminotransferase (PPAT), adenyl succinate lyase (ADSL), adenyl succinate synthetase isozyme-1 (Adss1), inosine-5′-monophosphate dehydrogenase (IMPDH), and guanine monophosphate synthetase (GMPS) was measured. The location of PRPSAP1 and PPAT in the liver was assessed by an immunofluorescence assay. Results: Metabolite profiling showed that the level of AMP, adenine, adenosine, hypoxanthine, and guanine was increased significantly. RNA-sequencing showed that gene expression of phosphoribosyl pyrophosphate synthase (PRPS2), phosphoribosyl glycinamide formyl transferase (GART), AICAR transformylase (ATIC), ADSL, Adss1, and IMPDH were raised, and gene expression of adenosine monophosphate deaminase 3 (AMPD3), adenosine deaminase (ADA), 5′,3′-nucleotidase, cytosolic (NT5C), and xanthine oxidoreductase (XOR) was also increased significantly. Fructose increased the gene expression, protein expression, and fluorescence intensity of PRPSAP1 and PPAT in mice livers by increasing mTOR expression. Fructose increased the expression and activity of XOR, decreased the expression of uricase, and increased the serum level of UA. Conclusions: This study demonstrated that the increased purine de novo synthesis may be a crucial mechanism for fructose-induced hyperuricemia.